Implementation of Number Notation in Song Learning - Muhammad Dunia Rizki; Rina Maryanti; Verra Wulandary (Indonesian Journal of Multidiciplinary Research, 2023)
In the process of learning a song work, constraints often occur in students' limited memory. The song material given at the first meeting will be forgotten when reviewed at the second meeting, to overcome this we try to apply number notation as a way for students to recall the tone of the song that has been given. The purpose of this study was to determine the efficiency and response of the application of number notation to song learning in junior high school. This study uses a qualitative descriptive method, the data collection technique used in this study is to provide a pre-test and post-test which contains 10 questions regarding numerical notation. The findings of this study gave a positive response to the students, in the initial pre-test found results that were not good because many of the students did not understand numeric notation at all, but after that they were shown a video of reading material notation of numbers and then a post-test was carried out, the results were good. The students made progress after seeing the video. The conclusion of this study is to implement numeric notation in the song learning process, making it easier for students to memorize the material and making it easier for teachers in the process of conveying it, thus it is hoped that it can be a solution to the problems previously mentioned.